2007
DOI: 10.1097/jsa.0b013e318140002c
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Allografts: Indications and Outcomes

Abstract: Meniscal allograft transplantation was introduced into clinical practice now over 20 years ago for the treatment of the symptomatic postmeniscectomy patient who has not yet developed osteoarthritis. Over the years, the indications have been fine-tuned and certain risk factors for failure have been identified. As the number of publications increases steadily, we now know that meniscal allografting significantly reduces pain and improves function. Recent data also suggest a potential chondroprotective effect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…[6][7][8] Their importance to the integrity of the knee is acknowledged by the shift towards attempted repair and more recently meniscal replacement rather than debridement or excision. 9,10 Several authors have reported that partial or total meniscectomy has detrimental effects and leads to radiological evidence of osteoarthritis (OA) of the knee in up to 50% of patients between five and 15 years postoperatively. [11][12][13] Unfortunately variable inclusion and exclusion criteria, inconsistent reporting on coexisting pathology within the knee and a lack in standardised means of data collection and analysis, are factors that make drawing firm conclusions difficult.…”
mentioning
confidence: 99%
“…[6][7][8] Their importance to the integrity of the knee is acknowledged by the shift towards attempted repair and more recently meniscal replacement rather than debridement or excision. 9,10 Several authors have reported that partial or total meniscectomy has detrimental effects and leads to radiological evidence of osteoarthritis (OA) of the knee in up to 50% of patients between five and 15 years postoperatively. [11][12][13] Unfortunately variable inclusion and exclusion criteria, inconsistent reporting on coexisting pathology within the knee and a lack in standardised means of data collection and analysis, are factors that make drawing firm conclusions difficult.…”
mentioning
confidence: 99%
“…[1][2][3][4] Mid-and long-term studies have shown that medial and lateral allograft transplantation significantly reduces pain and improves the function of the knee. [5][6][7][8][9][10] Furthermore, successful outcome may be linked to the type of meniscus transplanted, with better results reported for lateral than for medial meniscal transplants.…”
mentioning
confidence: 99%
“…The cumulative survival rates for the medial and lateral meniscal allografts at 10 years were 74% and 70%, respectively [29]. Thus, the surgeon may expect an approximate survival of 70% of allografts at 10 years [30]. Several studies have reported the radiological outcomes of MAT [9].…”
Section: Discussionmentioning
confidence: 99%